2002
DOI: 10.1093/emboj/cdf625
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in hnRNP A/B expression during erythropoiesis mediates a pre-mRNA splicing switch

Abstract: A physiologically important alternative pre-mRNA splicing switch, involving activation of protein 4.1R exon 16 (E16) splicing, is required for the establishment of proper mechanical integrity of the erythrocyte membrane during erythropoiesis. Here we identify a conserved exonic splicing silencer element (CE 16 ) in E16 that interacts with hnRNP A/B proteins and plays a role in repression of E16 splicing during early erythropoiesis. Experiments with model premRNAs showed that CE 16 can repress splicing of upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 65 publications
(109 reference statements)
6
52
0
Order By: Relevance
“…In one example, hnRNP A1 and A2 were shown to repress exon 16 inclusion in the protein 4.1R transcript. Differentiation of erythroblasts accompanied an AS switch to exon 16 inclusion, a process that coincided with down-regulation of hnRNP A1 and A2 (Hou et al 2002). Because up-regulation of hnRNP A1/A2 appears to be shared by most if not all proliferating cells, it will be interesting to see if additional proliferation/ differentiation-associated changes in AS are the result of changes in hnRNP A1/A2 levels.…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%
“…In one example, hnRNP A1 and A2 were shown to repress exon 16 inclusion in the protein 4.1R transcript. Differentiation of erythroblasts accompanied an AS switch to exon 16 inclusion, a process that coincided with down-regulation of hnRNP A1 and A2 (Hou et al 2002). Because up-regulation of hnRNP A1/A2 appears to be shared by most if not all proliferating cells, it will be interesting to see if additional proliferation/ differentiation-associated changes in AS are the result of changes in hnRNP A1/A2 levels.…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%
“…This potential role in splicing regulation prompted us to test the impact of TRIM10/HERF1 downregulation on specific splicing factors, such as hnRNP A1, which is the only factor known to inhibit exon 16 inclusion [26]. Immunoblotting experiments showed that the modulation of TRIM10/HERF1 expression does not seem to affect hnRNP A1 expression (Supplementary information, Figure S1), suggesting that TRIM10/HERF1 most likely acts through an hnRNP A1-independent pathway.…”
Section: Trim10/herf1 Knockdown Blocks Both Hemoglobin Production Andmentioning
confidence: 99%
“…Spot 2352 contained hnRNP A/B, an RNA-binding protein that regulates selective splicing of premature mRNA, such as protein 4.1R that is required for erythropoiesis [36]. The circadian clock is known to regulate splicing of presenilin-2 mRNA in the mouse liver, and it is predicted that the alternative splicing of presenilin-2 may affect its function [37].…”
Section: Rna-binding Proteinmentioning
confidence: 99%